2014
DOI: 10.1055/s-0034-1383363
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour Efficacy of Piper tuberculatum and Piplartine Based on the Hollow Fiber Assay

Abstract: Piper tuberculatum, popularly known in Brazil as "jaborandi falso" and "pimenta darta", is widely used in folk medicine for the treatment of several diseases. In this study, the in vivo hollow fiber assay was used to investigate the antitumour efficacy of the crude extract and piplartine obtained from P. tuberculatum roots. Human glioblastoma (SF-295) and colon carcinoma (HCT-8) cell lines were used. In vitro cytotoxicity was assayed by the MTT assay. In the hollow fiber assay, nude mice implanted with tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
16
0
3
Order By: Relevance
“…Therefore, it can be concluded that analogue 10 induced oxidative stress that was restored by overexpressed PRDX4 in cultured U87MG cells. Due to this, 1 was found to be less effective in SF-295 human glioblastoma cells as compared to HCT-8 human colon carcinoma cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that analogue 10 induced oxidative stress that was restored by overexpressed PRDX4 in cultured U87MG cells. Due to this, 1 was found to be less effective in SF-295 human glioblastoma cells as compared to HCT-8 human colon carcinoma cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piplartine is an amide alkaloid found in several Piper species (Piperaceae). It has been shown that piplartine has potential anticancer properties [9,10]. Piplartine also shows benefits in the treatment of the parasitic infection schistosomiasis, caused by helminth flatworms of the genus Schistosoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…Piplartine (piperlongumine) is a plant-derived compound found in some Piper species that became a novel potential antineoplastic agent. Potent cytotoxicity, genotoxicity, antitumor, antiangiogenic and antimetastatic properties, in addition to presenting adequate bioavailability and safety profile have been attributed for this molecule and its derivatives [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . Although its cytotoxic properties have been known for over three decades, the great interest in this molecule has arisen after its cytotoxicity and ability to induce the production of reactive oxygen species (ROS) selectively in cancer cells were described [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%